The Sponge-Derived Brominated Compound Aeroplysinin-1 Impairs the Endothelial Inflammatory Response through Inhibition of the NF-κB Pathway - Vidal-Valenzuela, Isabel; Castilla-Ruiz, Laura; Marrero-Capitán, Ana Dácil; Bravo-Ruiz, Inés; Bernal-Muñoz, Manuel; Manrique-Poyato, María Inmaculada; Rodríguez-Quesada, Ana María; Medina-Torres, Miguel Ángel; Martínez-Poveda, Beatriz Amparo (MDPI, 2022)
Aeroplysinin-1 (Apl-1) is a brominated compound isolated from the marine sponge Aplysina aerophoba that exhibits pleiotropic bioactive effects, impairing cell growth in cancer cells, inhibiting angiogenesis in vitro and in vivo and modulating the redox status of different cell types, among other reported activities. In addition to the aforementioned effects, the anti-inflammatory po- tential of this natural compound was explored in previous work of our laboratory, but the mechanism of action underlying this effect was not described. In this work, we delve into the anti-inflammatory effect of Apl-1 in the context of vascular endothelial cells in vitro, providing new data regarding the molecular mechanism underlying this activity. The characterization of the mechanism of action points to an inhibitory effect of Apl-1 on the NF-κB pathway, one of the main axes involved in endothelial response during inflammatory events. Our results show that Apl-1 can inhibit the ex- pression of pro-inflammatory genes in tumor necrosis factor alpha (TNF-α)- and lipopolysaccharide (LPS)-stimulated human umbilical vein endothelial cells (HUVECs), targeting the nuclear factor kappa B subunit (NF-κB) pathway through a mechanism of action involving the inhibition of I kappa B kinase (IKK) complex phosphorylation and RelA/p65 nuclear import. In addition, Apl-1 prevented the phosphorylation of Akt induced by TNF-α in HUVECs, probably supporting the inhibitory effect of this compound in the NF-κB pathway. Experimental evidence reported in this work opens the door to the potential pharmacological use of this compound as an anti-inflammatory agent in diseases that course with a pathological endothelial response to inflammation, such as atherosclerosis.
Keywords: Inflamación; Células endoteliales; metabolitos derivados de esponjas marinas; Ruta NF-κB; Ruta PI3K/Akt; Aterosclerosis